The Conditions of and Requirements for the Formation of Clusters in Biotechnology - Domonkos, David (Competitio, 2011)
In this article, with the help of the value chain model, I explain the functioning of biotech clusters. The “cluster” phrase was originally defined by Porter. In my opinion, the problem with Porter’s and other classical definitions of a cluster is that they are static, whereas the main feature of clusters’ is actually their dynamic nature. This is the reason why the following should also be included in the definition: – clusters emerge in a turbulent way: processes cannot be foreseen due to the lack of linearity. – a cluster, however, is a kind of an arena, because dense and changing vertical input-output relations and connections between horizontal organizations always generate a sort of a need for change. – clusters cause changes in the innovation policy, as they support the evolution of a policy which is appropriate for cluster formation. That is, they act as catalysts for the formation of better conditions. Accordingly, Porter’s original definition needs modification. JEL classification: O32, L25, L65, D80